Health Disparities and Differences in Health-Care-Utilization in Patients With Pulmonary Arterial Hypertension - Park, Da-Hee; Meltendorf, Tanja; Kahl, Kai G.; Kamp, Jan C.; Richter, Manuel J.; Hoeper, Marius M.; Olsson, Karen M.; Fuge, Jan (Frontiers in Psychiatry, 2022)
Introduction Mental disorders are common in patients with pulmonary arterial hypertension (PAH) and contribute to impaired quality of life (QoL). The impact of mental disorders on access to health care, differences in clinical parameters and treatment in patients with PAH is unclear. In this study we sought to assess the impact of mental disorders and other health disparities on health-care-utilization in patients with PAH. Methods In a cross-sectional observational study of patients with PAH, mental disorders were characterized using a structed clinical interview. In addition, patients completed a self-administered questionnaire to assess QoL, symptoms of anxiety and depression, lifestyle-factors and educational status. Number of outpatient visits and communication events per year were calculated as a surrogate for health-care-utilization and were compared by the presence of mental disorder. Linear regression analysis was conducted to assess the impact on health-care-utilization. Results 117 patients with PAH participated in this study (70% female, median age 59 (interquartile range, 49–70) years). Significant differences between patients with or without mental disorders were found in anxiety, depression and QoL. There were no significant differences in clinical parameters. Patients with mental disorders had higher rates of outpatient visits and communication events than patients without mental disorders. Linear regression revealed a gain of 2.2 communication events per year in the presence of any mental disorders. Conclusion Mental disorders in patients with PAH are common and significantly affect health-care-utilization. This higher demand in patients with mental disorder needs to be addressed by physicians, psychiatrists and specialized nurses offering therapeutic strategies.